2017
DOI: 10.3389/fgene.2017.00111
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of the Human Gut Microbiome Reveals a Broad Distribution of Metabolic Pathways for the Degradation of Host-Synthetized Mucin Glycans and Utilization of Mucin-Derived Monosaccharides

Abstract: The colonic mucus layer is a dynamic and complex structure formed by secreted and transmembrane mucins, which are high-molecular-weight and heavily glycosylated proteins. Colonic mucus consists of a loose outer layer and a dense epithelium-attached layer. The outer layer is inhabited by various representatives of the human gut microbiota (HGM). Glycans of the colonic mucus can be used by the HGM as a source of carbon and energy when dietary fibers are not sufficiently available. Both commensals and pathogens c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 161 publications
(244 reference statements)
4
86
0
Order By: Relevance
“…Functionally, in humans, the loose outer layer of the mucosal surface provides an area where the inhabiting bacteria can avoid washout from the flow of fluids through the intestinal tract. It also provides a source of energy for commensal bacteria that are able to degrade mucin glycans by releasing glycosyl hydrolases (Ravcheev & Thiele, ). The data presented here indicate that this may also be the case for the C. apella NHP.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, in humans, the loose outer layer of the mucosal surface provides an area where the inhabiting bacteria can avoid washout from the flow of fluids through the intestinal tract. It also provides a source of energy for commensal bacteria that are able to degrade mucin glycans by releasing glycosyl hydrolases (Ravcheev & Thiele, ). The data presented here indicate that this may also be the case for the C. apella NHP.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that RS supplementation, at least for the Ruminococcaeae family, results in a shift from fibrolytic family members to amylolytic family members that are well known butyrateproducers (Ruminococcus bromii, Ruminococcus torques). Typically, in the absence of sufficient dietary fibers, commensal and pathogenic bacteria start to forage on mucin glycans to harness carbon and energy (51,52).…”
Section: Potential Mechanisms Of Rs Actionmentioning
confidence: 99%
“…Although direct mother‐to‐child bacterial transmission significantly contributes to the establishment of the neonatal microbiome, feeding pattern also has a major influence . Because gut microorganisms have differing abilities to utilize different types of glycans as carbon sources for growth and metabolism, differences in milk glycans may also affect the composition of the gut microbiome in the offspring. It has been shown that the milk N‐glycans of secretory immunoglobulin A (sIgA) and lactoferrin are affected by GDM, but not the HMOs .…”
Section: Introductionmentioning
confidence: 99%